Psychological Well-Being Keluarga yang Memiliki Kerabat Orang dengan Gangguan Jiwa (ODGJ) di Desa Tempursari Kabupaten Lumajang - Maulidah, Lailatul; Cholilah, Indah Roziah (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2024)
Families who have relatives with mental illness should get positive and non-discriminatory social support. However, in reality, there are still many families who have not provided full support to sufferers because these families often experience stigma and discrimination from the surrounding environment, sometimes even from their surrounding community. This can have a negative impact on the family's psychological well-being. However, it turns out that there are still families who show strengthening despite being stigmatized by the community. This can have a good impact on the psychological well-being of the family. The focus of the problems in this study are: 1. How is the description of psychological well-being in families who have relatives of people with mental disorders (ODGJ) in Tempursari Village, Lumajang Regency? 2. What are the factors that influence the psychological well-being of families who have relatives of people with mental disorders (ODGJ) in Tempursari Village, Lumajang Regency? This research uses a qualitative approach that is descriptive narrative, analyzing the description of the psychological well-being of families who have relatives of People with Mental Disorders (ODGJ). The data collection techniques used semi-structured interviews, observation, and documentation. The result of the research is that the description of the subject's psychological well-being can be said to be good in several dimensional aspects and less good in several other dimensional aspects. Factors that can affect the subject's psychological well-being are social support, evaluation of life experiences, religiosity, and marital status.